2017
DOI: 10.1007/s12603-016-0752-8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-aging effect of riboflavin via endogenous antioxidant in fruit fly Drosophila melanogaster

Abstract: Riboflavin prolonged the lifespan and increased the reproduction of fruit flies through anti-oxidative stress pathway involving enhancing the activity of SOD1 and CAT and inhibiting LF accumulation. Riboflavin deserves more attention for slowing human aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 32 publications
0
33
0
1
Order By: Relevance
“…Oxidative stress is a key effect of aging and degenerative diseases along with aging. The authors have demonstrated that supplementation of RF significantly extended the lifetime and strengthened the reproduction of fruit flies via enhancing the activity of antioxidant enzymes [11]. RF also activates the synthesis of a normal extracellular matrix and reduces reactive oxygen species (ROS) levels in keratoconus [12].…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is a key effect of aging and degenerative diseases along with aging. The authors have demonstrated that supplementation of RF significantly extended the lifetime and strengthened the reproduction of fruit flies via enhancing the activity of antioxidant enzymes [11]. RF also activates the synthesis of a normal extracellular matrix and reduces reactive oxygen species (ROS) levels in keratoconus [12].…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…Anti-aging in Drosophila melanogaster (fruit fly) RF at 120 µg/mL SOD1 ↑; CAT ↑; lipofuscin (LF) ↓ RF prolonged the life span and increased reproductive capacity through anti-oxidative stress pathway involving enhancing the activity of SOD1 and CAT and inhibiting lipofuscin accumulation [11] Keratoconus corneal stroma cells RF with selenium administration protected against GTN-induced brain oxidative toxicity by protecting brain MMCA activity, inhibiting free radicals and supporting the antioxidant redox system. [19] Migraine model RF 100 mg/kg was treated before GTN-induced migraine Lipid peroxidation↓, GSH↑ RF and vitamin E had a protective effect on the GTN-induced brain injury by inhibiting free radical production, regulation of calcium-dependent processes, and supporting the antioxidant redox system.…”
Section: Dose Antioxidant Enzymes Key Findings Referencesmentioning
confidence: 99%
“…Huangfu et al (2013) employed fruit fly model system to test the antiaging effects of astaxanthin-rich alga (Haematococcus pluvialis) in which it markedly enhanced their lifespan and reduced the age-related decline in locomotor function. Zou et al (2017) studied the antiaging effect of riboflavin in fruit fly model system and found that riboflavin significantly extended the lifespan and reproduction of fruit fly by elevating superoxide dismutase 1 (SOD1) and catalase (CAT). Moreover, fruit fly was used to demonstrate the improvement of methionine sulfoxide reductase activity under the oxidative stress conditions by feeding methyl-cysteine fortified meals (Wassef et al, 2007).…”
Section: Fruit Fly Modelmentioning
confidence: 99%
“…Yet, the negative effect can be prevented by antioxidants. The combined vitamin B supplementation causes a marked decrease in ROS, protein oxidation, and an enhancement of antioxidative enzymes [9,[14][15][16]. Subjects continuously exposed to low-grade oxidative stress, such as manual laborers [17] and patients suffering from schizophrenia [18] or chronic illnesses including cancer, might particularly benefit from the antioxidant and anti-inflammatory impact of the vitamin B in the prevention of lipid peroxidation [19,20].…”
Section: Introductionmentioning
confidence: 99%